The current state of swedish housing: Ongoing trends in multifamily residential construction in Gothenburg municipality - Johansson Ågren, Tomas (My University, 2023)
This thesis is a contribution to - Building permits Gothenburg 2021, an ongoing series by CBA that explores what is being built right now. It aims to provide food for thought and discussion of our contemporary multifamily residential architecture and its trends. It does so by peering into the collection of granted building permits, often seen one by one, but not as a whole. The approved multifamily residential projects of 2021 in Gothenburg could be summed up with the metrics of 56 permits with a total of 6073 pages, and 4945 apartments divide onto approximately 450 000 square meters of Gross area. This tells us that the city is growing, but it doesn’t nourish our curiosity of how, where and with what it grows. Fortunately, scrutinizing those 6073 pages does. Together they form a crystal ball, or a road map into our near future, detailing how and where we will live. And something is happening. The question of where the city is developing is examined by introducing a novel way to visualize in which direction Gothenburg grows. Backed up by exploring the municipality’s strategy for expansion and the political ambition to add housing to the north-east part of the city. The investigation reveals that the set goals likely are met. However, on average two thirds of the apartments end up in the southern parts of the city, with Sydväst literally shattering their target. The thesis also asks the question of what trends can be seen in the permits, and there are several. On a positive note, 2021 sees more projects with a larger diversity of apartments-types and a larger share of three- or more-bedroom apartments. On the other hand, there is a continued increase in the share of the smallest apartment-type, the studio apartment. There is also a rise in what can only be described as monocultures, entire projects only containing one apartment-type. Lastly it asks how our buildings and apartments are developing. And there are reasons to worry. One of them is that 45 percent of the apartments found in the permits are single sided. This is a result of an increasing number of apartments per level. This, coupled with shrinking apartment sizes and a market that strives for the minimum regulatory requirements, tells a story of an ongoing loss of quality in our smallest dwellings.
Keywords: building permits, Gothenburg, residential architecture, dwelling space qualities, statistics